Young anatomists perceptions of aorta-celiac trunk models and their use in anatomical education training. - Bedre Duygu, Ozden; Govsa, Figen; Oner, Serkan; Cabar, Nesibe; Oner, Zulal; Akderya, Tarkan (Surgical & Radiologic Anatomy, 2025)
Background: Anatomical variations of the aorta-celiac trunk are highly relevant in abdominal surgery and interventional radiology. Traditional CT-A images may fall short in conveying these complex structures. This study investigates whether patient-specific 3D models can enhance resident-level understanding of aorta–celiac trunk anatomy and support surgical education. Methods: In this study, CT-A images of 1,000 adults aged between 18 and 60 were evaluated. Celiac trunk patterns were classified into eight types, and 3D solid models were created for each. In this study, seven residents were presented with eight stations, each showcasing an aorta-celiac trunk pattern in both CT-A and 1:1 scale solid model formats. The participants were asked to assess each format individually, identifying the variations, describing structural characteristics, and evaluating their educational value. Results: The vascular origin measurement values, when compared to the actual anatomical values of the corresponding cases, showed that the models were 1:1 identical replicas. According to the survey results, although 85.71% of the residents were aware of 3D printing and anatomical models, they lacked knowledge about the computer programs used to create these models. All residents agreed that the aorta-celiac trunk models enhanced their understanding of the vascular source and improved pattern recognition when compared to conventional cross-sectional CT-A imaging. Eight carousel-based stations provided qualitative assessments, with results showing the usefulness of celiac trunk models when used as anatomical tools for detecting pattern type (p = 0.018), determining the number of branches of the celiac trunk (p = 0.026), visualizing celiac trunk variations more clearly (p = 0.017), clearly observing the diameters of branches arising from the celiac trunk (p = 0.043), understanding the presence of variations in the celiac trunk (p = 0.018), and effectively explaining celiac trunk variations to residents (p = 0.018). Across all cases, participants' scores for understanding anatomical variations were significantly higher when using the 3D model; moreover, residents judged the 3D models to be substantially more useful than conventional twodimensional CTangiography slices for studying the celiac trunk. Conclusion: 3D aorta-celiac trunk models can improve anatomy education by offering tangible, high-fidelity representations that enhance visuospatial understanding. These models provide clear, demonstrative feedback, allowing learners to accurately grasp complex anatomical relationships. Specifically, the plastic-like material used to replicate celiac trunk vascular structures enables precise visualization of the origin, branching patterns, shapes, and angles—facilitating a well-structured and spatially coherent learning experience.